The Relationship between Health Administration Practices and Quality of Patient Care: A Review (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Many believe improved health administration procedures improve patient care. However, administrative procedures affect patient care in many ways, and hospitals are complicated systems. This global quantitative study examines the relationship between health administration practices and hospital care quality. Web of Science, Global Health, EconLit, EMBASE, and PubMed were thoroughly searched without language or country restrictions. Our empirical study statistically examined the relationship between administrative processes and many high-quality patient care features. Medication and equipment availability, clinical quality (treatment protocol adherence), health results, and patient pleasure or experience were examined. Every association observed in the study was statistically favourable, substantially negative, or null at 5%. Only 28 of 10,284 studies met inclusion criteria and exhibited modest bias. We have cross-sectional and intervention-based studies from high, poor, and medium-income countries. Of the 124 associations recorded, 61 (49.2%) were considerably positive, three (2.4%) were strongly negative, and 60 (48.4%) were empty. Health outcomes (59%), structural quality (75%) and clinical quality (62%) were most associated, but patient satisfaction (78%) was not. Administrative approaches may improve certain aspects of care, however the results demonstrate a mixed evidence base with roughly equal proportions of positive and null effects. Randomised research designs are rare, resulting in weak causal findings. This suggests that intervention studies and natural experiments, utilising quantitative health administration methodologies, are needed to investigate the favourable relationships in many domains.